Efeito do extrato aquoso de folhas de Polymnia sonchifolia (yacon) em ratas diabéticas - Volpato, G. T. [UNESP]; Vieira, F. L. [UNESP]; Damasceno, D. C. [UNESP]; Câmara, Francisco Luiz Araújo [UNESP]; Di Stasi, L. C. [UNESP]; Lemonica, I. P. [UNESP] (My University, 2007)
Polymnia sonchifolia is a medicinal plant used as hypoglycemic agent and other ends. The aim was to evaluate the yacon effect on diabetes in Wistar female rats, which was divided in 4 groups: non-diabetic (n=24) given (gavage) 32.4 mg kg -1 of an aqueous extract of plant (treated group) or vehicle (non-treated group), and one diabetic group (n=24) with similar treatment compared to non-diabetic rats. Diabetes was induced using streptozotocin (i.v. route, 40 mg kg -1). Glycemia was monitored after rodent adaptation period, 15 days after diabetes induction, and each 10 days after yacon/vehicle in early treatment. During experiment period, body weights, food and water intake were daily measured. The rats (non-diabetic or diabetic) given yacon extract treatment presented no significant difference related with glycemia, body weight gain, and food and water intake. Thus, further studies such increase of rat number in agreement with different glycemic levels and increase of the plant extract dose are necessary.
Effects of leaves of Polymnia sonchifolia (yacon) aqueous extract in diabetic rats
Keywords: Diabetes mellitus; Polymnia sonchifolia; Rat; Streptozotocin; Yacon; antidiabetic agent; herbaceous agent; Polymnia sonchifolia extract; streptozocin; unclassified drug; animal experiment; animal model; body weight; controlled study; diabetes mellitus; drug effect; female; fluid intake; food intake; glucose blood level; medicinal plant; nonhuman; rat; streptozocin diabetes; weight gain; Rattus; Rodentia